PHYSIOTHERAPY MANAGEMENT ON POST ANTERIOR CRUCIATE LIGAMENT (ACLR) DEXTRA: A CASE STUDY - Fatimah As-Syifa Khairunnisa; Wijianto; Sigit Saputro (CV. Fahr Publishing, 2025)
This study aims to determine the results of physiotherapy management performed on post-anterior cruciate ligament reconstruction (ACLR) patients. This is a case study method with one sample of post-ACLR dextra patient in phase I. this research evaluates pain using the numeric rating scale (NRS), range of motion (ROM) with goniometer, muscle strength with manual muscle test (MMT), and Lysholm Knee Scoring for functional ability. The physiotherapy management provided to the patient includes Transcutaneous Electrical Nerve Stimulation (TENS), ice compression (cryotherapy), patellar mobilization, heel slide exercise, gait training, and strengthening exercise. From three physiotherapy sessions conducted, the results showed a decrease in resting and pressure pain, as well as an increase of knee ROM. However, no changes were found in movement pain and functional ability evaluations from the first to the third session.